2012
DOI: 10.1186/1471-2180-12-239
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of bacterial TonB-dependent signaling in the generation of an oligogalacturonide damage-associated molecular pattern from plant cell walls exposed to Xanthomonas campestris pv. campestris pectate lyases

Abstract: BackgroundEfficient perception of attacking pathogens is essential for plants. Plant defense is evoked by molecules termed elicitors. Endogenous elicitors or damage-associated molecular patterns (DAMPs) originate from plant materials upon injury or pathogen activity. While there are comparably well-characterized examples for DAMPs, often oligogalacturonides (OGAs), generated by the activity of fungal pathogens, endogenous elicitors evoked by bacterial pathogens have been rarely described. In particular, the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 99 publications
0
20
0
Order By: Relevance
“…Interestingly, several CWDEs are associated with TonB-dependent transporters (TBDTs) forming specific carbohydrate utilization (CUT) systems (14,20,34,39). The pectate lyase activity of Xcc depends on the exbD2 gene, which belongs to the TonB-ExbBD system and is required for the induction of HR on pepper through production of pectin-derived oligogalacturonides acting as DAMPs (139). This association may represent a specific adaptation of xanthomonads to their host plants.…”
Section: A Diverse Enzymatic Arsenal To Degrade the Host Cell Wallmentioning
confidence: 99%
“…Interestingly, several CWDEs are associated with TonB-dependent transporters (TBDTs) forming specific carbohydrate utilization (CUT) systems (14,20,34,39). The pectate lyase activity of Xcc depends on the exbD2 gene, which belongs to the TonB-ExbBD system and is required for the induction of HR on pepper through production of pectin-derived oligogalacturonides acting as DAMPs (139). This association may represent a specific adaptation of xanthomonads to their host plants.…”
Section: A Diverse Enzymatic Arsenal To Degrade the Host Cell Wallmentioning
confidence: 99%
“…One gene, exbD2 , distinguished the TonB operon found in Xanthomonas spp. from that of most other bacterial genera and is essential for pathogenicity and induction of bacterial pectate lyase activity (34, 35). Interestingly, we found that in addition to the TonB system, the entire Xps type II secretion cluster was recombinant among the pepper pathogenic strains of SC3.…”
Section: Discussionmentioning
confidence: 99%
“…In Xanthomonas campestris pv. campestris, the strain deficient in exbD2, which encodes a component of its unusual elaborate TonB system, had impaired pectate lyase activity and caused no visible symptoms for defense on the non-host plant pepper (Vorhölter et al, 2012). It seems possible that extracellular enzyme productions of Xag may be regulated by other iron uptake pathway.…”
Section: Discussionmentioning
confidence: 99%